Vasculitis In Practice (IntechOpen, 2023)
"Vasculitis" describes an inflammatory process that involves the blood vessels and contributes to vascular damage. Autoimmunity, infections, drugs, and malignancies have been considered among potential etio-pathogenic factors. In vasculitis, the inflammation might develop in either a systemic or an organ-specific form and might exist as an independent pathology "primary vasculitis" or as a presentation of an existing primary pathology, that is, "secondary vasculitis". This book Vasculitis In Practice-An Update on Special Situations - Clinical and Therapeutic Considerations unlike many publications in the field, uses a different evidence-based approach to organ-specific vascular inflammatory diseases. The authors highlighted the unmet needs from the 1994 Chapel Hill Consensus Conference introducing the latest clinically relevant definitions for the different forms of vasculitis revised in 2012. The identification, classification, and management of kidney disease with different types of vasculitis with an evidence-based update on proposed therapeutic strategies are presented in this publication.